Development of a strategy for the production of docosahexaenoic acid by Schizochytrium sp. from cane molasses and algae-residue. (January 2019) - Yin, Feng-Wei; Zhu, Si-Yu; Guo, Dong-Sheng; Ren, Lu-Jing; Ji, Xiao-Jun; Huang, He; Gao, Zhen
Highlights: Algae-residue from Schizochytrium sp. was used as nitrogen source to replace yeast extract. Cane molasses was used as carbon source to substitute glucose. Two-stage culture with different carbon sources increased the efficiency of DHA production. This work offers a strategy to reduce waste by-products discharge and cut production costs. Abstract: The aim of this work was to reduce the algae-residue emission and make use of cane molasses as fermentation materials for docosahexaenoic acid (DHA) fermentaion by Schizochytrium sp., which further could cut the cost of DHA production. Algae-residue and cane molasses were respectively used as nitrogen and carbon sources to replace yeast extract and glucose. A significant DHA yield of 18.58 g/L was obtained using algae-residue, while cane molasses could not be used well as sole carbon source due to the presence of undesirable substance. A two-stage culture strategy with glucose followed by pretreated cane molasses as carbon source was developed, resulting in a final DHA yield of 15.22 g/L. This study therefore offers an economical and green strategy for DHA production by Schizochytrium sp.